Different Targeting Ligands-Mediated Drug Delivery Systems for Tumor Therapy - Shuxin Yan; Jintong Na; Xiyu Liu; Pan Wu (Pharmaceutics, 2024)
Traditional tumor treatments have the drawback of harming both tumor cells and normal cells, leading to significant systemic toxic side effects. As a result, there is a pressing need for targeted drug delivery methods that can specifically target cells or tissues. Currently, researchers have made significant progress in developing targeted drug delivery systems for tumor therapy using various targeting ligands. This review aims to summarize recent advancements in targeted drug delivery systems for tumor therapy, focusing on different targeting ligands such as folic acid, carbohydrates, peptides, aptamers, and antibodies. The review also discusses the advantages, challenges, and future prospects of these targeted drug delivery systems.